ANALISIS AKULTURASI DAKWAH DAN KEBUDAYAAN PADA MASA KENABIAN MUHAMMAD - wawan sopiyan; Mukhlis Mukhlis; Solimin Solimin (Jurnal khabar: Komunikasi dan Penyiaran Islam, 2020)
In highlighting the portrait of Da'wah practiced by the Messenger of Allah in several periods, it can be said that the missionary mission that was being carried out at that time was not an easy activity, in the course of Islamic history recorded, that the da'wah carried out by Muhammad, encountered many obstacles and obstacles, due to internal conditions humanity and the aqeedah of Arab society in general are in a state that is far from the teachings that Muhammad is broadcasting. Therefore, the da'wah process that will be applied really requires a mature strategy, especially the condition of the people who are accustomed to doing past activities and practices such as consuming alcohol, gambling, fighting power, adultery, adultery to murder.